Role of board and firm performance in determination of CEO compensation: Evidence from Islamic republic of Pakistan - Muhammad Usman; Waheed Akhter; Adeel Akhtar (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
The current research aims to investigate the influence of board effectiveness and firm performance on CEO compensation within the context of developing economy of Islamic Republic of Pakistan. The study uses Partial Least Square (PLS) based Structural Equation Modeling (SEM) Technique to draw the inference using PLS Graph Version 3.0. It uses Karachi Stock Exchange (KSE)-100 index companies as a sample for the period of five years 2007-2011. Before analyzing the structural model the validity and reliability of the model is confirmed through bootstrapping technique and variance inflationary factor respectively. The structural model results reveal that board effectiveness has negative influence on CEO compensation. Opposite to agency theory and current studies from developed countries, we have found a negative association between the firm performance (firm value and firm profitability) and CEO compensation. These results are due to different business environment of Pakistan and poor corporate governance structure. So, it is concluded that board of directors of Pakistani companies are not that much effective to facilitate the objective determination of CEO compensation and failed to design such contracts which can link the CEO pay with firm performance. Our results also support the international literature that firm size is the major determinant of CEO compensation. Most of the previous studies have been conducted with reference to developed economies so we need to know the procedure through which the corporate managers in developing economies are compensated. The unique characteristics of Pakistani business environment like concentrated ownership, family owned businesses and poor governance structure make it interesting to study this issue. Moreover, unlike developed economies the CEO compensation does not include stock options as a part of the total compensation representing the difference in CEO compensation contracts with respect to developed economies and developing economies. So, current study makes a valuable addition to the available literature by investigating the issue within the context of unique business environment of Pakistan.
Keywords: 330